EVLT with foam sclerotherapy for varicose veins: a single unit study - D., Wasim M.; Pasha, Azeez; Rao, U. Vasudeva; Reddy, Venkatesh; Rai, Sai Shruthi; Shampur, Sanjitha (International Surgery Journal, 2018)
Background: The true incidence of varicose veins in our country is not known as majority of patients with mild to moderate varicosities do not report to the physicians and only patients with complication like eczema, ulceration and bleeding are seen in clinics and hospitals. The search for a more effective means of prevention and for the perfect cure for this common condition continues. The aim of this study was to assess feasibility of Endovenous laser therapy with foam sclerotherapy for varicose veins with SFJ/SPJ incompetence. Methods: Out of two hundred and fifty (n = 250), the most common age group was between 31-40 years. 68% were females. Left limb was more affected. The patients presented with varied symptoms, out of which painless dilated and tortuous veins was most common. Long Saphenous system was the most common venous system affected by varicosity. The median operating time for one system was 35 mins. Visual analog scale for pain (VAS) was median 1 at 24 hours. 25 patients had pain for 2 weeks, 30 patients had ecchymosis, 45 patients had neuralgia, 35 patients had pain, none of the patients had skin burns and one (1) patient developed DVT. Mean hospital stay was 1 day. Follow up at 3 months showed, no pain and no scar. Results: In this retrospective study, we found that incidence of colorectal carcinoma is more between 40-60 years of age with male predominance; lymph node metastasis is more than metastasis in any other sites. CT scan can diagnose lymphatic metastasis and infiltration in surrounding tissue more accurately. Percentage of sphincter saving procedure were low in rectal malignancies in our study. Conclusions: At present, endovenous laser ablation with Foam Sclerotherapy of both the GSV and SSV shows considerable promise in the treatment of varicose veins. Avulsion is not required. The advantages of this procedure include ease, safety, cosmesis and durability.